Progress in Self-humidifying Technology of Proton Exchange Membrane Fuel Cells: A Comprehensive Review of Multi-scale Structure Design and Material Modification - Xu, Renfu; Li, Wenxin; Yin, Hao (International Journal of Electric Power and Energy Studies, 2025)
The performance and lifetime of proton exchange membrane fuel cells (PEMFC) are highly dependent on the wetting state of the membrane, and the phenomenon of "membrane drying" can lead to serious problems such as decreased proton conductivity, increased heat production and even membrane tearing. In order to reduce the dependence on external humidification system, self-humidification technology at the battery level has become a research hotspot in recent years. This paper systematically reviews the methods of self-humidification by adjusting the structure of internal components (flow field, membrane, catalytic layer, gas diffusion layer) and material modification, including the key progress in the past five years. The results show that the water distribution uniformity can be significantly improved by optimizing the flow field design (such as bionic flow field and porous metal foam flow field). The introduction of inorganic/organic additives (such as CeO₂, MOF) or the use of bipolar membrane design can effectively improve water retention and proton conductivity; The functional modification of the catalytic layer and gas diffusion layer (such as oxide load and gradient pore structure) further enhances the operating stability under low humidity conditions. Although self-humidifying technology has advantages in reducing system volume and cost, it still faces challenges such as material compatibility, long-term durability, and inadequate water management for high current density. Future research should focus on multi-scale collaborative optimization, the development of new materials and the performance verification under actual working conditions to promote the wide application of PEMFC in portable devices and new energy vehicles.